2014
DOI: 10.1111/ajo.12259
|View full text |Cite
|
Sign up to set email alerts
|

Risks and benefits of hysteroscopy and endometrial sampling as a standard procedure for assessing serendipitous findings of endometrial thickening in postmenopausal women

Abstract: A retrospective study was undertaken of 35 asymptomatic postmenopausal women undergoing hysteroscopy, dilatation and curettage (H D&C) for an incidental finding of thickened endometrium to assess the rate of significant pathological findings, cost per finding and complication rate of any procedures performed. This study found one case of endometrial adenocarcinoma (1/35; 3%) at an estimated cost per significant finding of $507,116 with an estimated 11.6 complication events per finding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…The estimated cost of one hysteroscopy and D&C procedure is AUD$2614 including operating theatre, anaesthetics, medical labour, supplies, allied health, pathology, imaging and pharmacy costs. 4 In asymptomatic postmenopausal women, a low threshold for investigation may be unnecessary and may be potentially harmful.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The estimated cost of one hysteroscopy and D&C procedure is AUD$2614 including operating theatre, anaesthetics, medical labour, supplies, allied health, pathology, imaging and pharmacy costs. 4 In asymptomatic postmenopausal women, a low threshold for investigation may be unnecessary and may be potentially harmful.…”
Section: Introductionmentioning
confidence: 99%
“…Inpatient D&C is an invasive procedure that requires general anaesthesia and carries risks such as uterine and bowel perforation, contributing to patient anxiety and potentially serious patient outcomes as well as significant healthcare costs. The estimated cost of one hysteroscopy and D&C procedure is AUD$2614 including operating theatre, anaesthetics, medical labour, supplies, allied health, pathology, imaging and pharmacy costs 4 . In asymptomatic postmenopausal women, a low threshold for investigation may be unnecessary and may be potentially harmful.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there is no consensus nor guidelines regarding treatment of postmenopausal endometrial polyps[ 19 , 20 ]. Aston et al [ 21 ] have reported that endometrium polyps are benign lesions which are most frequently detected in asymptomatic postmenopausal women, and suggested that routine practice of D&C in asymptomatic postmenopausal women should be re-evaluated. Bel et al [ 22 ] reported that malignancy was detected in 30/631 (4.75%) patients diagnosed with polyps by ultrasonography or diagnostic hysteroscopy prior to surgery.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite a high accuracy in diagnosis, there is no consensus regarding hysteroscopy for endometrial diagnosis because of the cost associated with this method[ 21 , 29 ] and the risks of surgical complications ( e.g ., uterine perforation, bowel damage, excessive fluid absorption, anesthetic complications)[ 30 ]. In the present study, hysteroscopies were performed in the women in a clinical setting without hospitalization, and this reduced the cost of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Hysteroscopic investigation, rather than dilatation and curettage is a widely accepted diagnostic method for of endometrial cancer. In a recent report, only one of 35 asymptomatic post-menopausal women with an endometrial thickness exceeding 4 mm presented with adenocarcinoma [1]. In a study of 268 women undergoing diagnostic hysteroscopy, Giannella reported only four cases of endometrial cancer and two cases of atypical endometrial hyperplasia [2].…”
Section: Introductionmentioning
confidence: 99%